Ministry of Agriculture - (:unkn) unknown (My University, 2011)
VISION STATEMENT A vibrant and dynamic agricultural sector, comprising small, medium and large market-driven agri-business enterprises; focused on maintaining an adequate level of food security and competitiveness; through the production of high quality agricultural produce, as well as the efficient use of resources and appropriate technologies; ably supported by an effective marketing system. MISSION To transform and reposition the Agricultural Sector in Barbados through the promotion of an agri-business approach to farming, with particular attention being paid to the effective use of resources, as well as the adoption of appropriate technology and sound management practices in order to achieve internationally competitive production, processing and marketing enterprises, which contribute significantly to social and economic development and food security, as well as to the sustainable management of the natural resource base of the country.
Keywords: Agriculture